Development of a Backend Architecture for an Online Mental Counselling Platform to Enhance Performance and Security - Misna Asqia (AI Society & STMIK Indonesia, 2025)
The increasing demand for mental health services during the COVID-19 pandemic emphasizes the importance of developing a web-based psychological counselling platform. This study aims to create a robust backend architecture to support the functional and non-functional requirements of an online mental counselling platform. The backend plays a crucial role in managing business logic, data management, user authentication, counselling session settings, and integration with third-party services. The Research and Development (R&D) methodology was implemented through the steps of requirements analysis, architecture design, module creation, and performance and security testing. The backend was built with a layered architecture approach, ensuring optimal load management, information security, and scalability. The application of authentication features with JSON Web Token (JWT) provides an extra layer of protection for user data. System tests were conducted using Postman through three main scenarios. The initial trial showed a